2010
DOI: 10.3141/2145-13
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Demand for Rural Intercity Transportation Services in a Changing Environment

Abstract: With higher fuel costs and changing economic conditions, travel behavior and the level and allocation of resources in highways, rail, air, and transit service in rural areas may be changing. The objective of this study is to determine the attitude of would-be passengers in their choice of mode and the factors determining their choice in rural and small urban areas. A stated preference survey was developed and administered to residents of North Dakota and northwest and west central Minnesota. The survey asked r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…The data shall be analyzed using the Statistical Package for Social Science Software (SPSS. 19), and the multinomial logit model for mode choice will develop to assess the relative importance of demographic, socio-economic and service attributes that influence travelers' choice behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data shall be analyzed using the Statistical Package for Social Science Software (SPSS. 19), and the multinomial logit model for mode choice will develop to assess the relative importance of demographic, socio-economic and service attributes that influence travelers' choice behavior.…”
Section: Methodsmentioning
confidence: 99%
“…It was concluded that the use of disaggregate, behavioral, stochastic models in a predictive framework is preferable to the aggregate approach because the predictions of disaggregate models are extremely promising. Subsequently, there were a large number of studies on disaggregate mode choice within the intercity context [5]- [19]. The studies contain probabilistic models which only focus on making a specific choice, once the traveler has decided to make a trip.…”
Section: Introductionmentioning
confidence: 99%
“…On-time schedule has a positive significant impact on transit choice (Outwater et al, 2011;Zhang et al, 2008) while Ahern and Tapley (2008) concluded that travel time with high reliability has no significant impact on travel mode choice. Moreover, other features of public transportation system such as travel costs, in-vehicle time, waiting time, egress and departure times, number of transfers and the possibility of seating affect the choice of people (Alberini, 2019;Mattson et al, 2010). Ben-Akiva and Morikawa (2002) found that different components of travel time including arrival time, waiting time, in-vehicle time and departure time have a significant effect on people's choices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Handy et al, 2010), attitudes and perceptions (e.g. Diana, 2010;Elias and Shiftan, 2012;Gatersleben and Appleton, 2007;Shiftan, 2008;Stradling, 2011) and familiarity and experience of the transport mode (Mattson et al, 2010;Stradling, 2011). Scherer (2010) and Scherer and Dziekan (2012) explored the reasons why travelers have a higher preference for rail transport in comparison to bus-system given a similar level of service.…”
Section: Determinantsmentioning
confidence: 99%